The impact of land use change on carbon storage and multi-scenario prediction in Hainan Island using InVEST and CA-Markov models - Lei, Jinrui; Zhang, Le; Chen, Zongzhu; Wu, Tingtian; Chen, Xiaohua; Li, Yuanling (Frontiers in Forests and Global Change, 2024)
As a fundamental element of global carbon storage, the storage carbon in terrestrial ecosystem is significant for climate change mitigation. Taking Hainan Island as an example, this paper employs the InVEST as well as the CA-Markov models to assess and predict how different land use affects carbon storage in various situations from 2000 to 2020 and from 2030 to 2050 on Hainan Island. The influence factors, together with driving mechanisms of carbon storage spatial distribution are quantitatively analyzed as well in this paper. The results demonstrate that, from 2000 to 2020, Hainan Island's carbon storage and density have decreased by 5.90 Tg and 1.75 Mg/hm2, respectively. The sharp rise in built land mainly makes the carbon storage decline. From 2030 to 2050, land use changes on Hainan Island are expected to result in differing degrees of carbon storage loss in various scenarios. In 2050, Hainan Island's carbon storage will decline by 17.36 Tg in the Natural Development Scenario (NDS), 13.61 Tg in the Farmland Protection Scenario (FPS), and 8.06 Tg in the Ecological Protection Scenario (EPS) compared to 2020. The EPS can efficiently maintain carbon sequestration capability, but it cannot effectively prevent cropland area loss. Regarding the carbon storage’s spatial distribution, Hainan Island generally exhibits a pattern of high carbon storages in the low and middle carbon storages in the surrounding areas. Areas with high value are primarily located in Hainan Island's central and southern mountainous areas, whereas areas with low value are primarily located in surrounding areas with lower elevations. Geographic detection presented the spatial differentiation of carbon storage in Hainan Island is mainly influenced by factors like slope, land use intensity, and DEM, as well as its interaction with other factors is significantly strengthened (p<0.05). Under the strategic framework of the "carbon peaking and carbon neutrality" goal and the national ecological civilization pilot zone, it is imperative to carefully consider scenarios for ecological protection and farmland protection, adopt ecological regulation models with spatial differentiation, and implement land use policies to improve ecosystem stability, which will contribute to carbon storage loss reduction and ensure food and ecological security.